TEHL Analysis of Rough Surface Spur Gears with Non-Newtonian Lubricants under Sudden Overloads - Mongkolwongrojn MONGKOL; Panichakorn JESDA (My University, 2012)
The time-dependent modified Reynolds equation, elasticity equation, and energy equation with initial conditions were formulated and solved numerically using a multi-grid multilevel with full approximation technique for an involute spur gear. In this analysis, the normal load and sudden overload are applied on either two pairs or one pair of gear teeth. The transition from two pairs to one pair and vice versa are modeled as a step variation of load. The effects of overload, surface roughness, non-Newtonian lubricant properties of the meshing gear in the region along the line of action are examined. The results show that lubricant properties and surface roughness have significant effects on film thickness, film temperature and friction coefficient for spur gears with rough surfaces. The minimum film thickness is decreased rapidly with the decrease of lubricant power law index. For gears operated at a sudden overload condition, the film temperature and friction coefficient are severely increased.
Keywords: Spur; Gear and Bearing Dynamics Analysis